Finding Guide State - Taylor, Evelyn
The Robert Lagomarsino Collection Box Listing for the State of California papers acts as a finding guide to the content of the collection. It provides detailed information of the content, such as titles to publications, authors, dates of publications, and helpful notes for identification.